Pemisahan Butanol dari Campuran ABE Menggunakan Software Aspen Plus: Pengaruh Refluks Rasio terhadap Kandungan Butanol - Dennis Farina Nury; Pramahadi Febriyanto; Lisa Anggraini Ismi; Rahmat Taufik Hidayah (Politeknik ATI Padang, 2022)
Production of acetone-butanol-ethanol (ABE) through the fermentation process is one alternative that needs to be developed. Less economical in the ABE fermentation process is the difficulty of the separation process from the fermentation product and the by-products of the reaction. Among the separation process methods, such as extraction, distillation, adsorption, and gas stripping, the distillation method is still the most widely used method in the ABE separation process. The purpose of this study was to provide recommendations for predicting good ABE separation and producing optimum operating conditions to produce high % butanol content. Which is then simulated using Aspen Plus V11 software. This study varied the reflux ratio in the distillation column and the decanter operating temperature. The results showed that butanol purity reached 90.33% in the radfrac 1 column operated at a pressure of 1.3 atm with a reflux ratio of 5, the location of the 7th feed stage and the number of stages 11. Then proceed to the purification stage in the radfrac column 2 which is operated at a pressure of 2 atm with a reflux ratio of 5, the location of the 4th stage feed and the number of stages 5. The decrease in the reflux ratio of the radfrac column causes a decrease in the butanol content at the bottom so that the purity of butanol also decreases and decreases % recovery or recovery of butanol. This is also followed by the location of the feed stage, which is getting higher, and the number of stages is increasing.